(untitled) - Bratton, John; Grint, Keith (Mason, Ohio, 2005)
Title on accompanying CD-ROM: Leadership in organizations; Includes bibliographical references and index; Canada-Vietnam Education Network
Keywords: Leadership; Industrial management